Analysis and control of fungal deterioration on the surface of pottery figurines unearthed from the tombs of the Western Han Dynasty - Wang, Yu; Wang, Cen; Yang, Xinyu; Ma, Kaixuan; Guo, Peifeng; Sun, Qirui; Jia, Shili; Pan, Jiao (Frontiers in Microbiology, 2022)
In April 2020, 232 tombs of the Western Han Dynasty were found in Sundayuan, Heze City. In total, 141 pottery figurines of significant historical, cultural, and artistic value were unearthed from the tombs. Some of the figurines are currently being stored in warehouses, and the surface of some of the figurines show fungal deterioration. To thoroughly analyze the fungal deterioration on the surface of the pottery figurines and find appropriate control methods, we used high-through sequencing, scanning electron microscopy observation, pure cultures of culturable fungi, and optical microscopy observation and molecular identification of culturable fungi. We conducted fungistatic and simulation experiments in the laboratory to find appropriate control methods. We found that the fungi on the surface of the figurines were mainly of the phylum Ascomycota, and a few fungi were of the phyla Basidiomycota and Mucoromycota. We isolated seven culturable fungal strains and observed their colony morphology. The seven fungal strains were Lecanicillium aphanocladii, Penicillium aurantiogriseum, Clonostachys rosea, Mortierella sp., Mortierella alpina, Aspergillus flavus, and Cladosporium halotolerans. Through the fungistatic and simulation experiments conducted in the laboratory, we found that 50 mg/mL cinnamaldehyde and 0.5% K100 (2-methyl-4-isothiazolin-3-one) have a good fungistatic effect. They can not only inhibit the growth of fungi on medium, but also inhibit the growth of fungi on the surface of pottery figurines. This study has good reference significance for the analysis and control of fungal deterioration of unearthed pottery figurines.